(untitled) (REMUNOM, 2025)
This study aims to analyze the role of the obstetric nurse in promoting humanized childbirth, addressing their competencies, practices, and the importance of their role in maternal and infant healthcare. The literature review reveals that humanized childbirth prioritizes respect for women’s autonomy, individualized care, and the minimization of unnecessary interventions, fostering a welcoming and respectful environment. As a facilitator of this process, the obstetric nurse plays a fundamental role in providing emotional support, guidance, and care to the birthing woman, contributing to a more positive childbirth experience. However, the research also highlights challenges in implementing humanized childbirth, such as institutional barriers and the need for continuous and specific training for these professionals. The conclusions indicate that, to ensure an obstetric care model that prioritizes the dignity and well-being of women, it is essential to invest in the recognition and training of obstetric nurses. This study emphasizes the importance of further research and practices to overcome existing challenges and promote more effective and humanized childbirth care. The role of the obstetric nurse is, therefore, a key element in transforming obstetric care, ensuring the health and satisfaction of birthing women.